On the agricultural statistics of Ireland - Lawson, James A. (Statistical and Social Inquiry Society of Ireland, 1854)
Here is a vast mass of information, and it is surely worth while to endeavour to elicit the truths contained in it; and while this remains to be done, none of us need complain of a deficiency of materials for valuable statistical papers. It was this train of thought which induced me to attempt, in a hurried and imperfect manner, to bring before you some matters connected with the Irish Returns of Agricultural Statistics; and I may mention that a very interesting publication, illustrative of the view I have put forward, has appeared : "Cheshire's Results of the Census of Great Britain in 1851," which gives some of the most striking results of the census, presented in a mode likely to attract, and which has attracted popular attention. If the same kind of work were performed with respect to the Irish census, it would be found to repay the labour which it would require.
Read April 27th 1854
Keywords: Crop farming; Agricultural statistics; 314.15